Starting the synchronous motor in the PAP "Lisina" by a generator from the HPP "Vrla 1” - Stevanović, Ilija (Proceedings, Electrical engineering institute "Nikola Tesla", 2020)
This paper describes the testing that was done to balance the synchronous motor rotor in PAP "Lisina". For balancing to occur, it was necessary to slowly rotate the motor rotor to synchronous speed. This was done using one of the generators from HPP Vrla 1. The synchronous motor is driven asynchronously with a constant U/f ratio. Before that, the necessary parameters were calculated. The experiment is illustrated with timing diagrams of the process showing the stator speed, voltage and current as well as the current in the synchronous motor rotor during its run-in.
Keywords: synchronous motor, start, U/f regulation, rotor balancing